Barriers to Entry in Rail Passenger Services: Empirical Evidence for Tendering Procedures in Germany - Beck, Arne (European Journal of Transport and Infrastructure Research, 2011)
As in several other European Union Member States, Germany has used tendering to an increasing degree since the mid-1990s for subsidized passenger rail services. In order to determine whether market entry barriers exist in this market, a dataset of 30 German tendering procedures with start of operations between 1997 and 2007 is analyzed. The data consists of comprehensive primary data provided directly by public transport authorities and operators. On average 11 rail companies requested the tendering documents, but only four per tendering procedure submitted bids. The empirical analysis shows that there are two main tendering conditions that clearly influence the number of bidders. The first is the percentage of risk assumed by the public transport authority for price increases on input factors like personnel or fuel. This shows a positive correlation with the number of bidders. The second is the level of revenue risk to be assumed by the operator, which shows a negative correlation. Both correlations are highly significant. Authorities in Germany as well as in other countries using the tendering instrument should be aware of the influence of uncertainty and therefore avoid imposing untenable risks on operators. A high level of uncertainty will reduce authorities’ efficiency gains by reducing competition and making it necessary for operators to calculate an increased risk premium.